ENEM in times of Pandemic: challenges faced by teachers in the face of remote education of the state network of President Kennedy /TO - Gularte, Fabiana Nunes (2021)
With the global situation (pandemic) that we are experiencing, during this period that reaches more than a year and a half, the area of education suffered a great impact and had to change with a new form of teaching so that students would not lose the bond with school, which took place through online classes and scripts in a fortnightly way. This article addresses the challenges faced by teachers in the pandemic in relation to ENEM and analyzes the competencies and skills  through the methodologies worked in remote education by the teachers of the public school of President Kennedy-TO, with a focus on preparing for the National High School Exam - ENEM. A questionnaire was conducted in which 10 teachers working in teaching answered objective and subjective questions related to the methodologies used and changes that were suffered during the pandemic. The results obtained show that with the pandemic the preparation of students for The ENEM has become quite challenging, and teachers have been trying to reinvent themselves in various ways  so that students reach the skills and abilities required in this exam.